Comparison of Monochromatic Ocular Aberrations Measured with an Objective Cross-Cylinder Aberroscope and a Shack-Hartmann Aberrometer - HONG, XIN; THIBOS, LARRY N.; BRADLEY, ARTHUR; WOODS, RUSSELL L.; APPLEGATE, and RAYMOND A. (Optometry and vision science, 2003)
Repeated measures of wavefront aberrations were taken along the line-of-sight of seven eyes using two instruments: an objective, cross-cylinder aberroscope (OA) and a Shack-Hartmann (SH) aberrometer. Both instruments were implemented on the same optical table to facilitate interleaved measurements on the same eyes under similar experimental conditions. Variability of repeated measures of individual coefficients tended to be much greater for OA data than for SH data. Although Zernike coefficients obtained from a single measurement were generally larger when measured with the OA than with the SH, the averages across five trials were often smaller for the OA. The Zernike coefficients obtained from the two instruments were not significantly correlated. Radial modulation-transfer functions and point-spread functions derived from the two sets of measurements were similar for some subjects, but not all. When average Zernike coefficients were used to determine optical quality, the OA indicated superior optics in some eyes, but the reverse trend was true if Zernike coefficients from individual trials were used. Possible reasons for discrepancies between the OA and SH measurements include difference in sampling density, quality of data images, alignment errors, and temporal fluctuations. Multivariate statistical analysis indicated that the SH aberrometer discriminated between subjects much better than did the objective aberroscope.